RUMAH TRADISIONAL BATAK TOBA MENUJU KEPUNAHAN : Suatu Analisis Antropologis - Antono, Yustinus Slamet (LOGOS, 2005)
The progress of science and technology give a great effect to human culture. New inventions or methods, either they are beneficial or not for human life, slowly put aside the people way of life is the which has already been practiced along the centuries or even take its place. One of the richness of Indonesian cultures is that there are so many kinds of traditional houses. It is one of the identities of tribes. Almost in all places in Indonesia, the forms of the traditional house-buildings are changing, even some of them are going to be disappeared. This article is a result of research on a changing culture, especially that of orientation of the Bataks in building their dwelling. Through library research on the traditional-house building of Toba Batak’s and studies on theory of culture and field research, this article describes the causal factors of the decreasing of the traditional-house building among the Toba Bataks.